Gender Divisions of Paid and Unpaid Work in Contemporary UK Couples. (April 2020) - McMunn, Anne; Bird, Lauren; Webb, Elizabeth; Sacker, Amanda
This article uses data from the UK Household Longitudinal Study to describe how contemporary British couples divide a range of work types. Our findings support the hypothesis, suggested by previous authors, that a shared egalitarian ideology is required for gender equality in divisions of work. In response to bargaining theories, the article also hypothesises that differentials in educational attainment within couples are more strongly associated with gender divisions of work when a couple's gender ideology is in conflict. Interaction analysis does not support this hypothesis.